Evaluation of Antipsychotic Drug Use in Paranoid Schizophrenia Patients - Herwidhiya Azizah (GLOBAL HEALTH SCIENCE GROUP, 2025)
One of schizophrenia’s treatment is pharmacological therapy using antipsychotic. This study aims to determine the demographic description (age, gender and length of stay), determine the pattern of antipsychotic drug use, determine the level of appropriateness of antipsychotic drug therapy based on the right patient, the right indication, the right drug, the right dose, and the right interval of administration based on the Rational Drug Use Module and Drug Information Handbook 27th Edition and determine the reduction in the final symptoms of schizophrenia patients after receiving antipsychotic drug therapy at the Inpatient Installation of dr. Soeharto Heerdjan Mental Hospital Jakarta for the period January - June 2023. The research method used is descriptive, with cross sectional design. Data collected retrospectively and using purposive sampling techniques. The study analyzed 95 prescription samples, showing that schizophrenia is more experience in in the range of 26-35 years old (44,21%) and in men (67.37%). The most common antipsychotic use was the atypical combination antipsychotic with the percentage of 37.5%. The single atypical antipsychotic most commonly prescribed is atypical antipsychotic with the percentage of 57.15%. The results showed that the appropriateness of the use of antipsychotics in correct patient is in 100%, correct indication is in 100%, correct drug is in 100%, correct dose is in 97.89% and the exact dosing interval of drug is in 92.63%. There was a decrease in schizophrenia symptoms in patients after undergoing hospitalization as seen from the decrease in Positive and Negative Syndrome Scale-Excited Component (PANSS-EC) scores with an average percentage decrease of 48%. This difference is clinically effective because the decrease exceeds 19– 28 %.